2011
DOI: 10.1523/jneurosci.6565-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar-Dependent Learning in Larval Zebrafish

Abstract: Understanding how neuronal network activity contributes to memory formation is challenged by the complexity of most brain circuits and the restricted ability to monitor the activity of neuronal populations in vivo. The developing zebrafish (Danio rerio) is an animal model that circumvents these problems, because zebrafish larvae possess a rich behavioral repertoire and an accessible brain. Here, we developed a classical conditioning paradigm in which 6-to 8-d-old larvae develop an enhanced motor response to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 20 publications
(17 reference statements)
4
85
1
Order By: Relevance
“…The use of perceptual timing tasks that allow investigation of how the fish perceives the duration of a stimulus or a sequence of stimuli is more plausible given the current technical limitations. A perceptual timing task can also be combined with restricted tail movement as some previous studies have shown promising results (CS -US conditioning in [69] and CS-entrained rhythms in [70]) in young larval fish, with minimum training required. It is also possible to train a larval fish in a different environment before imaging and then record the brain calcium signals to the same stimulus under a microscope, but this depends on how well a fish can generalize what it learned across different contexts.…”
Section: Future Interval-timing Studies Using Zebrafishmentioning
confidence: 99%
“…The use of perceptual timing tasks that allow investigation of how the fish perceives the duration of a stimulus or a sequence of stimuli is more plausible given the current technical limitations. A perceptual timing task can also be combined with restricted tail movement as some previous studies have shown promising results (CS -US conditioning in [69] and CS-entrained rhythms in [70]) in young larval fish, with minimum training required. It is also possible to train a larval fish in a different environment before imaging and then record the brain calcium signals to the same stimulus under a microscope, but this depends on how well a fish can generalize what it learned across different contexts.…”
Section: Future Interval-timing Studies Using Zebrafishmentioning
confidence: 99%
“…Darland and Dowling, 2001;Sison and Gerlai, 2010;Bianco et al, 2011) and to forage in response to synthetic chemicals (Braubach et al, 2009). Young larvae (6-8 dpf ) can similarly be trained to exhibit tail-flicking behavior in response to light by pairing it with touching by a probe (Aizenberg and Schuman, 2011). The ability to perform associative learning increases with age.…”
Section: Larvae Learn To Sense Flowmentioning
confidence: 99%
“…Nonassociative forms of learning, such as habituation and sensitization, were successfully shown in larval zebrafish (Best et al, 2008). However, associative forms of learning were only shown in a few studies at later developmental stages (Aizenberg and Schuman, 2011). The advantages of using early-stage zebrafish larvae include the large amount of offspring and the translucency of the animals, which allows for various in vivo imaging techniques visualizing neural activity during the actual behavior.…”
Section: Introductionmentioning
confidence: 99%